دراسة تأثير سم النحل (HBV, Apis mellifera) على بروتينات البلازما البشرية ومعدل تخثر الدم (Journal of the College of Basic Education, 2025)
The present study was conducted at the National Center for Hematology Research and treatment in (2023) and it demonstrates the effect of bee venom (HBV, Apis mellifera) on human plasma proteins and blood coagulation rate. The effect of bee venom on blood clotting in humans was compared for both sexes (males and females) to determine the extent of the effect of gender on blood clotting time. The results indicated a correlation between the concentration of bee venom and the duration of blood clotting in females, where the highest significant effect was recorded for the concentration of bee venom at 100% at the 0.05 level, for a time period of 25 minutes.